Analisis Pengaruh Teman Sebaya terhadap Perolehan Jumlah Hafalan Al-Qur’an pada Kelas A Tahfidz For Kidz PP. Qur’anan ‘Arobiyya Kota Kediri - Maziyyatul Muslimah; Anni Muslimah Abwa (Insititut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study is to find out the condition of peers and how it affects the number of Qur'an memorization in class A Tahfidz For Kidz PP Qur'anan 'Arobiyya. The research method used is a qualitative research method in the form of analysis and conclusions that depend on the sharpness of research analysis. Conducted in class A Tahfidz For Kidz PP Qur'anan 'Arobiyya with a population of 13 children. As we know that every child has different abilities in memorizing abilities, but every child can improve these abilities by paying attention to situations and conditions when memorizing. Especially the conditions when interacting with peers which greatly affect the acquisition of the number of memorizing the Qur'an obtained.